2007
DOI: 10.1007/s00221-007-0989-x
|View full text |Cite
|
Sign up to set email alerts
|

Quantifying the effects of voluntary contraction and inter-stimulus interval on the human soleus H-reflex

Abstract: The human soleus H-reflex is commonly tested as an indicator of the reflex excitability of the calf muscles with infrequent stimuli to a subject seated and at rest. However, the reflex varies widely with the level of voluntary contraction and with the time history of stimulation. We studied two aspects of this variation. Antagonist (tibialis anterior) activation decreases the response, while increasing agonist (soleus) activation increases the H-reflex to a peak after which it declines. In subjects with large … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

9
97
1

Year Published

2008
2008
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 84 publications
(107 citation statements)
references
References 41 publications
9
97
1
Order By: Relevance
“…One potential concern with this protocol is that such stimulation intervals may have induced homosynaptic postactivation depression, a reduction in neurotransmitter release from Ia terminals due to repeated activation (Hultborn et al 1996), and thereby reduced the size of the successive H reflexes. The influence of this mechanism, however, is minimized during voluntary contractions for stimulation rates up to 4 Hz (Burke et al 1989;Stein and Thompson 2006;Stein et al 2007). Moreover, when the size of each H reflex within a train was compared with that of the first H reflex of the train, no trend indicating a significant involvement of homosynaptic postactivation depression was noted.…”
Section: Test H Reflexes and Conditioned H Reflexesmentioning
confidence: 97%
“…One potential concern with this protocol is that such stimulation intervals may have induced homosynaptic postactivation depression, a reduction in neurotransmitter release from Ia terminals due to repeated activation (Hultborn et al 1996), and thereby reduced the size of the successive H reflexes. The influence of this mechanism, however, is minimized during voluntary contractions for stimulation rates up to 4 Hz (Burke et al 1989;Stein and Thompson 2006;Stein et al 2007). Moreover, when the size of each H reflex within a train was compared with that of the first H reflex of the train, no trend indicating a significant involvement of homosynaptic postactivation depression was noted.…”
Section: Test H Reflexes and Conditioned H Reflexesmentioning
confidence: 97%
“…The H reflex undergoes less HD when the test motoneuron pool is voluntarily active (Burke et al 1989;Rothwell et al 1986;Stein et al 2007). It has been suggested that HD is not functionally important (Stein et al 2007).…”
mentioning
confidence: 99%
“…It has been suggested that HD is not functionally important (Stein et al 2007). However, on the one hand, short-term skilled training depresses HD of the H reflex for Ͼ24 h (Meunier et al 2007), and this mechanism could underlie the smaller H reflex after long-term skilled training in ballet dancers compared with controls .…”
mentioning
confidence: 99%
“…If one H-reflex is induced in a resting state subject, then later stimulation will produce reflexes with lower amplitudes at intervals of up to 10 s. Amplitude depression is termed post-activation depression or homosynaptic depression 9,10,11,12 . The degree of depression depends on the interstimulus time: the shorter the time, the more obvious the depression 13 .…”
mentioning
confidence: 99%
“…In contrast, the depression is not obvious when the stimulation intervals are 8 s or longer 7 . Decreased synaptic neurotransmitter release may be responsible for the depression, which is most obvious in resting individuals and is weak or absent when the tested muscle is voluntarily activated 8,10 .…”
mentioning
confidence: 99%